Metacognitive strategies in university students: A review in Iberoamerica - Cancino Vargas , Naysha Lucero (2024)
Learning is an elementary process in the life of each student, which is why different strategies have been used throughout history to achieve it in a more effective way. Metacognitive strategies have the objective of regulating and controlling our own learning and, in this way, learning more easily and effectively. Given this situation, the question arises of how metacognitive strategies influence the learning of university students, where the main objective has been to describe this influence in university education at the Hispanic American level in the last 10 years. The method that has been used has been a systemic review of 38 review articles, considering, after purification, 18 articles were selected for the sample. This article has been prepared as part of the research process of the postgraduate thesis “Metacognitive strategies and academic performance in students of the VII cycle of the Monterrico Public Pedagogical Higher Education School.